Edible plant oils modulate gut microbiota during their health-promoting effects: a review - Zou, Qi; Chen, Ao-Qiu; Huang, Jing; Wang, Mei; Luo, Jiang-Hong; Wang, An; Wang, Xiao-Yin (Frontiers in Nutrition, 2024)
Edible plant oils are widely used in cooking, cosmetics, health supplement capsules and other industries, due to their various health-promoting effects. There is increasing evidence that edible plant oils can modulate gut microbiota during their health-promoting effects in animal experiments and cohort or clinical studies. However, the information concerning the gut microbiota modulation of edible plant oils during their health-promoting effects is scattered. In this article, the research progress on gut microbiota modulation of edible plant oils (especially camellia oil, olive oil and flaxseed oil) is summarized. Meanwhile, the summary on correlations between modulated gut microbiota and changed biochemical indexes is provided. The alterations of edible plant oils on gut microbiota-derived metabolites, and the correlations between altered metabolites and modulated gut microbiota as well as changed biochemical indexes are reviewed. Furthermore, the prospects for gut microbiota modulation of edible plant oils during their health-promoting effects are put forward. Existing literatures have shown that edible plant oils could modulate gut microbiota during their health-promoting effects, and some differential gut microbiota biomarkers were gained. Some similarities and differences existed while the oils exhibited health-promoting actions. Dosage and treatment time have influences on gut microbiota modulation of edible plant oils. Different edible plant oils exhibited different behaviors in modulating gut microbiota, and edible plant oils were mostly different in modulating gut microbiota compared to edible animal oils. Moreover, the modulated gut microbiota was significantly correlated with the changed biochemical indexes. Furthermore, edible plant oils altered SCFAs and other gut microbiota-derived metabolites. The altered metabolites were obviously correlated with the modulated gut microbiota and changed biochemical indexes. This review is helpful to the future research and application of edible plant oils in health-promoting effects from the perspective of gut microbiota.